The Effects on Offspring of Diabetes Mellitus Induced by Chemical Agents in Rats with Advanced Pregnancy - Canli, N.; Ozkan, H. A.; Risvanli, A. (Univ West Indies Faculty Medical Sciences, 2021)
Background: Gestational diabetes mellitus is an increasingly frequent metabolic disorder that is important for both baby and mother. New studies on the development and treatment of the disease are required. Objective: To investigate the effects on offspring's survival and the biochemical values of diabetes mellitus, induced by different doses of two chemical agents among 35 rats with advanced pregnancy. Methods: The rats were randomly divided into five groups, with the rats in Group 1 as the control group. Alloxan was administered intraperitoneally at doses of 40 and 60 mg/kg in Groups 2 and 3, respectively. Streptozotocin was injected intraperitoneally at doses of 40 and 60 mg/kg in Groups 4 and 5, respectively. Deliveries were monitored, and offspring numbers, survival rates and congenital anomalies were recorded. At the end of the study, blood was drawn from one female offspring in each group; glucose, total protein, albumin, triglyceride, cholesterol, calcium and phosphorus levels were measured, and inter-group comparisons were made. Diabetic agents administered at various doses prolonged the duration of pregnancy. Results: Offspring's deaths were most frequent in the alloxan groups. The number of offspring mortalities in the streptozotocin group was higher than that of the control group, but lower than that of the alloxan group. No differences in glucose, total protein, albumin, triglyceride, cholesterol, calcium and phosphorus levels were observed between the groups. These results indicate that the female offspring, born from rats with gestational diabetes mellitus induced by different chemicals, were only clinically affected. No effect of the type of chemicals on the results was found. Conclusion: The use of streptozotocin in the studies on female offspring born from rats with gestational diabetes mellitus is recommended.
Keywords: Alloxan; diabetes mellitus; offspring; rat; streptozotocin